Small Group Discussion Berbasis Peer Assesment: Meningkatkan Keterampilan Komunikasi Lisan Calon Guru Sekolah Dasar - Irma Pravitasari; Christina Ismaniati (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2019)
This research is conducted to improve oral communication skills of elementary school pre-service teachers through the application of small group discussion methods based on peer assessment. This research is a classroom action research. Data collection techniques used are peer assessment and observation. Pre-action conditions show the percentage of students who meet the criteria for skilled oral communication by 22.5%, after the first cycle of action the percentage of students increases to 52.2% and returns to increase in the action of cycle II with a percentage of 75%. Based on the results of these studies, it is known that the application of the peer group based small group discussion method can improve the oral communication skills of elementary school pre-service teachers. Penelitian ini dilakukan untuk meningkatkan keterampilan komunikasi lisan calon guru sekolah dasar melalui penerapan metode small group discussion berbasis peer assesment. Penelitian ini merupakan penelitian tindakan kelas. Teknik pengumpulan data yang digunakan adalah peer assesment dan observasi. Kondisi pratindakan menunjukkan persentase mahasiswa yang memenuhi kriteria terampil berkomunikasi lisan sebesar 22,5%, setelah tindakan siklus I jumlah persentase mahasiswa meningkat menjadi 52,2% dan kembali meningkat pada tindakan siklus II dengan persentase 75%. Berdasarkan hasil penelitian tersebut maka diketahui bahwa penerapan metode small group discussion berbasis peer assesment dapat meningkatan keterampilan komunikasi lisan calon guru sekolah dasar.